Strategi Dakwah dalam Surah Al-Muddatstsir Ayat:1-7 (Analisis Tafsir Sinar Karya Buya Malik Ahmad) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the characteristics and methodology of Buya Malik Ahmad's interpretation in Tafsir Sinar and identify the da'wah strategies contained in Surah Al-Muddatstsir verses 1–7. This study is important because Nusantara interpretation has contributed to presenting a contextual understanding of the Qur'an that is relevant to the socio-religious dynamics of Indonesian society. The study uses a qualitative approach with a library research type. Primary data comes from Tafsir Sinar by Buya Malik Ahmad, while secondary data are obtained from various books, journal articles, and relevant literature. Data are collected through documentation techniques and analyzed using descriptive-analytical methods. The results show that Tafsir Sinar uses the tahlili method by combining the bil ma'tsur and bil ra'yi approaches, with an adabi ijtima'i character, and presents a communicative and contextual interpretation. An analysis of Surah Al-Muddatstsir verses 1–7 yields six main da'wah strategies: proactive da'wah, theocentric orientation, self-purification, value differentiation, sincerity, and mental resilience. These findings indicate that da'wah, from Buya Malik Ahmad's perspective, is not only oriented toward conveying religious messages but also toward developing the spiritual, moral, and psychological qualities of the da'wah as an agent of social change.